A new Phyllomedusa Wagler (Anura, Hylidae) with reticulated pattern on flanks from Southeastern Brazil - Giaretta, Ariovaldo A.; de Oliveira Filho, Júlio C.; de C. Kokubum, Marcelo N. (Zootaxa, 2007)
We describe a new species of Phyllomedusa with reticulated pattern on the flanks from the State of Minas Gerais and provide data on its advertisement call, habitat, and tadpole. The new species differs from other species of the Phyllomedusa hypochondrialis group in color pattern, size, advertisement call, and breeding site. Phyllomedusa oreades topotypes and P. megacephala differ from the new species by lacking a reticulate pattern bordering the upper jaw and encircling the eyes. In P. ayeaye and P. itacolomi the hidden parts of legs present circular cells while in the new species this pattern is barred. The call of the new species has shorter notes than that of P. megacephala. The new species is smaller than P. centralis, P. megacephala, and P. itacolomi. From P. oreades topotypes, the new species differs also by presenting a broader reticulated stripe on flanks; a better defined reticulated pattern on throat, belly and ventral surfaces of hind limbs, and less projected nostrils. In life, the new species present dark blue reticulation on flanks, not black as in P. centralis, gray as in P. ayeaye or deep purple as in P. itacolomi. The new species is a pond breeder while P. centralis, P. megacephala and P. oreades are stream breeders. It can be distinguished from the remaining species of the P. hypochondrialis group by presenting a reticulate pattern bordering the upper jaw and eyes and orange cells with dark blue reticulations on flanks.